The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1139/f08-205
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of road access on lake trout (Salvelinus namaycush) populations: regional scale effects of overexploitation and the introduction of smallmouth bass (Micropterus dolomieu)

Abstract: In lake trout (Salvelinus namaycush) lakes of northeastern Ontario, Canada, aerial surveys of fishing activity on individual lakes (N = 589) and quantitative gillnet surveys (N = 65) were used to assess the effects of road access on angling effort and the presence of introduced smallmouth bass (Micropterus dolomieu). Angling effort, particularly during the open-water season, was highest and often exceeded estimated sustainable levels on lakes with good road access. Approximately 25% of the remote lakes also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Therefore, policies that are successful in one context may not maintain quality fishing and ensure long-term sustainability across a landscape where effort varies. Since many recreational fisheries are embedded in lake districts, equivalent to multistock, spatially structured fisheries (Post et al 2008;Hunt and Lester 2009;Kaufman et al 2009), we expect to see variation in effort across space and therefore variable success of common harvest policies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, policies that are successful in one context may not maintain quality fishing and ensure long-term sustainability across a landscape where effort varies. Since many recreational fisheries are embedded in lake districts, equivalent to multistock, spatially structured fisheries (Post et al 2008;Hunt and Lester 2009;Kaufman et al 2009), we expect to see variation in effort across space and therefore variable success of common harvest policies.…”
Section: Introductionmentioning
confidence: 99%
“…Aerial surveys were used to collect midday activity count (MAC) data to estimate angler effort following standard protocols developed for provincial fisheries monitoring programs (Kaufman et al, 2009;Lester et al, 1991;McGuiness et al, 2000). Aerial surveys of anglers were distinct from aerial surveys of cormorants.…”
Section: Angler Harvestmentioning
confidence: 99%
“…The midday activity bias factor values (K m ) ranged from 1.1 to 1.3 and were selected for each lake from values presented in Parker et al (2006) based on fish community (lake trout, walleye or multi-species targeted) and day-type (weekend vs weekday; Kaufman et al, 2009). For the ice-fishing season, parameter values used were: N = 90 (64 weekdays; 26 weekend days); T = 10 h; p = 2; K m ranged from 1.0 to 1.2.…”
Section: Angler Harvestmentioning
confidence: 99%
“…Roads are essential for forest management and also provide access for recreation, but there is concern about potential undesirable effects on wildlife and remote fisheries (e.g., Rempel et al 1997, Kaufman et al 2009, Bowman et al 2010. Rempel et al (1997) showed that the small, dispersed harvest blocks recommended to produce habitat for moose in northwestern Ontario actually resulted in a lower density of moose than areas with larger harvest blocks, likely because the relatively dense road network needed for small blocks increased hunter access.…”
Section: Minimizing Transportation Costsmentioning
confidence: 99%